2022
DOI: 10.3389/fbioe.2022.834270
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effects of tPRK, FS-LASIK, and SMILE on the Cornea

Abstract: Purpose: The objective of this study is to evaluate the in vivo corneal biomechanical response to three laser refractive surgeries.Methods: Two hundred and twenty-seven patients who submitted to transepithelial photorefractive keratectomy (tPRK), femtosecond laser-assisted in-situ keratomileusis (FS-LASIK), or small-incision lenticule extraction (SMILE) were included in this study. All cases were examined with the Corvis ST preoperatively (up to 3 months) and postoperatively at 1, 3, and 6 months, and the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
2
19
1
Order By: Relevance
“…Our results indicated that the decreases in DCRs with SMILE were greater than those observed with FS-LASIK in a matched comparison study. Unlike our results, Xin et al 20 showed a greater decrease in stiffness with FS-LASIK than SMILE in low to moderate myopia at 6 months after surgery. This difference can be related to different follow-up times.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results indicated that the decreases in DCRs with SMILE were greater than those observed with FS-LASIK in a matched comparison study. Unlike our results, Xin et al 20 showed a greater decrease in stiffness with FS-LASIK than SMILE in low to moderate myopia at 6 months after surgery. This difference can be related to different follow-up times.…”
Section: Discussioncontrasting
confidence: 99%
“…In our opinion, there is room for improvement in the predictive models. Although only preoperative IOP NCT and IOP GAT played a significant role in the predictive models, it seems that there should be more parameters involved, such as corneal biomechanics ( Xin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on IOP among patients undergoing laser-assisted in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK) ( Chang and Stulting, 2005 ; Kohlhaas et al, 2006 ; Yang et al, 2006 ; Pepose et al, 2007 ; Johannesson et al, 2012 ; Han et al, 2013 ; Schallhorn et al, 2015 ; Sales-Sanz et al, 2016 ), while limited literature reports exist on predictive models of IOP changes after small incision lenticule extraction (SMILE) ( Li et al, 2016 ; Shen et al, 2016 ). As a flapless procedure utilizing a small incision, SMILE preserves the integrity of the corneal tissue (including Bowman’s layer) and serves a better corneal biomechanics than LASIK ( Wang et al, 2022 ), although it does not preserve suspect corneas before iatrogenic ectasia ( Bao et al, 2022 ; Xin et al, 2022 ). The impact of SMILE on the corneal structure prompts changes in the IOP that might differ from other refractive surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies report that LVC compromise the biomechanical strength of the cornea [1][2][3][4][5][6]. However, the change in corneal biomechanics is strongly related to the refractive surgery technique and ablation profile.…”
Section: Methods Of Selected Corneal Refractive Surgery Proceduresmentioning
confidence: 99%